LYMPHOPARIETAL INDEX IN ESOPHAGEAL CANCER IS STRONGER THAN TNM STAGING IN LONG-TERM SURVIVAL PROGNOSIS IN A LATIN-AMERICAN COUNTRY - FIGUEROA-GIRALT,Manuel (2020)
ABSTRACT Background: The identification of prognostic factors of esophageal cancer has allowed to predict the evolution of patients. Aim: Assess different prognostic factors of long-term survival of esophageal cancer and evaluate a new prognostic factor of long-term survival called lymphoparietal index (N+/T). Method: Prospective study of the Universidad de Chile Clinical Hospital, between January 2004 and December 2013. Included all esophageal cancer surgeries with curative intent and cervical anastomosis. Exclusion criteria included: stage 4 cancers, R1 resections, palliative procedures and emergency surgeries. Results: Fifty-eight patients were included, 62.1% were men, the average age was 63.3 years. A total of 48.3% were squamous, 88% were advanced cancers, the average lymph node harvest was 17.1. Post-operative surgical morbidity was 75%, with a 17.2% of reoperations and 3.4% of mortality. The average overall survival was 41.3 months, the 3-year survival was 31%. Multivariate analysis of the prognostic factors showed that significant variables were anterior mediastinal ascent (p=0.01, OR: 6.7 [1.43-31.6]), anastomotic fistula (p=0.03, OR: 0.21 [0.05-0.87]), N classification (p=0.02, OR: 3.8 [1.16-12.73]), TNM stage (p=0.04, OR: 2.8 [1.01-9.26]), and lymphoparietal index (p=0.04, RR: 3.9 [1.01-15.17]. The ROC curves of lymphoparietal index, N classification and TNM stage have areas under the curve of 0.71, 0.63 and 0.64 respectively, with significant statistical difference (p=0.01). Conclusion: The independent prognostic factors of long-term survival in esophageal cancer are anterior mediastinal ascent, anastomotic fistula, N classification, TNM stage and lymphoparietal index. In esophageal cancer the new lymphoparietal index is stronger than TNM stage in long-term survival prognosis.